Women in Japanese Culture and Gender Diplomacy: The Evolution of Women's Roles in Japan's Foreign Service and Its Influence on the Regional Agenda - Athallah, Muhammad Hafiz; Putri, Sylvia Octa; Haryanti, Pitri; Fitria, Nur Khalida (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Given the growing importance of gender equality on a global scale, gender diplomacy has come to be seen as an important measure of a state's foreign policy legitimacy and efficiency. In light of this, this research explores the trends of the inclusion of women in terms of their leadership roles and policy-making capacities in Japan's Ministry of Foreign Affairs (Gaimushō) from 2015 to 2024, assessing its implications for the regional diplomacy of East Asia. Based on qualitative methodology, the analysis relies on secondary sources collected from the data of the MOFA, OECD, and WEF and assesses the application of "Womenomics" and the Women, Peace, and Security (WPS) initiative within the framework of traditional Japanese gender norms, which are reflected in the culture of the ie and Ryōsai Kenbo. As the results of the research reveal, even though the number of female participants in the Japanese labor market rose to 74.1% in 2024, women are still poorly represented in diplomatic positions, occupying just 5.1% of ambassadorial positions in 2023. These statistics demonstrate the persistence of institutional and cultural obstacles in the Japanese diplomatic service.